The physician-patient relationship in dialysis - Pinheiro,Joaquim (2013)
Introduction: Despite many technical and scientific advances in haemodialysis, the outcomes in patients with end stage renal disease are far from reaching the desired targets. How can they be improved? The doctor-patient relationship is a key issue in the healthcare provided to patients with end stage chronic kidney disease on dialysis. Patients and Methods: We, therefore, built a patient-centred biopsychosocial personalized approach to enhance patient autonomy and self-care as an alternative to the conventional medical approach to dialysis patients. We compared patient satisfaction achieved in both approaches using a patient satisfaction questionnaire, and we assessed the correlation between satisfaction and social, clinical and biological outcomes. Results and Conclusion: The alternative physician-patient relationship approach achieved better outcomes than the conventional one, and so it must be the choice approach for these patients